Nursing and euthanasia: A narrative review of the nursing ethics literature - Pesut, Barbara (Nurs Ethics, 2019)
BACKGROUND: Medical Assistance in Dying, also known as euthanasia or assisted suicide, is expanding internationally. Canada is the first country to permit Nurse Practitioners to provide euthanasia. These developments highlight the need for nurses to reflect upon the moral and ethical issues that euthanasia presents for nursing practice. PURPOSE: The purpose of this article is to provide a narrative review of the ethical arguments surrounding euthanasia in relationship to nursing practice. METHODS: Systematic search and narrative review. Nine electronic databases were searched using vocabulary developed from a stage 1 search of Medline and CINAHL. Articles that analysed a focused ethical question related to euthanasia in the context of nursing practice were included. Articles were synthesized to provide an overview of the literature of nursing ethics and euthanasia. ETHICAL CONSIDERATIONS: This review was conducted as per established scientific guidelines. We have tried to be fair and respectful to the authors discussed. FINDINGS: Forty-three articles were identified and arranged inductively into four themes: arguments from the nature of nursing; arguments from ethical principles, concepts and theories; arguments for moral consistency; and arguments from the nature of the social good. Key considerations included nursing’s moral ontology, the nurse–patient relationship, potential impact on the profession, ethical principles and theories, moral culpability for acts versus omissions, the role of intention and the nature of the society in which euthanasia would be enacted. In many cases, the same assumptions, values, principles and theories were used to argue both for and against euthanasia. DISCUSSION: The review identified a relative paucity of literature in light of the expansion of euthanasia internationally. However, the literature provided a fulsome range of positions for nurses to consider as they reflect on their own participation in euthanasia. Many of the arguments reviewed were not nursing-specific, but rather are relevant across healthcare disciplines. Arguments explicitly grounded within the nature of nursing and nurse–patient relationships warrant further exploration.